A cross sectional study to assess knowledge and self-expressed practices regarding universal precautions among nursing students - Khandelwal, Nisha; Negi, Parul; Kaur, Parminder; Kaur, Parwinder; Shruti; Nagi, Manisha (International Journal Of Community Medicine And Public Health, 2024)
Background: Each year, 2 million healthcare workers (HCWs) are exposed to HBV, 9 million to HCV and 1 lakh 70 thousand to HIV. To reduce disease transmission, blood and body fluid precautions were recommended in 1983 by the United States Centre for Disease Control (CDC). Objective was to assess the knowledge and Self-Expressed Practices (SEPs) regarding universal precautions among B.Sc. Nursing (BSN) students and the association between knowledge and SEPs. Methods: A descriptive approach and cross-sectional study design was used. A total of 200 students from BSN 1st year, 2nd year and 3rd years 60, 70 and 70, respectively, consented to participate in the study. Bio-data profile, a self-structured questionnaire to assess knowledge and a Likert scale to assess SEP. Results: Only 2.9% of students of BSN 2nd year fall in the adequate knowledge category, whereas 56.67 % (n=60) students of 1st year, 71.5% (n=70) students of 2nd year, and 68.6% (n=70) students of 3rd year belonged to moderate knowledge category. 86.67% of students in BSN 1st year, 78.57% of students 2nd year and 68.57% of students 3rd year fall in the adequate SEPs category. Only BSN 3rd year students showed a significant association between knowledge and SEPs sum total score (p=0.02). Conclusions: Maximum students had moderate knowledge, but SEPs were in an inadequate category. Students repeatedly receive training regarding universal precautions as they are the future of the health care system, and continuous surveillance of occupational hazards should be conducted to ensure safety and awareness among students and other Health Care Workers (HCWs).